Effects of Supplementation of Boric Acid in Dietary and Drinking Water on Performance, Incubation Characteristic and Intestinal Microbiota in Different Quail Varieties (Coturnix coturnix japonica) - Aslan, Sultan; Simsek, Ulku Gulcihan; Eroglu, Mehmet; Mutlu, Seda Iflazoglu (Wiley, 2025)
Background: Boric acid is an important alternative to antibiotics due to its positive effects on the immune system, endocrine system, lipid metabolism, mineral metabolism and energy metabolism. Different doses of boric acid supplemented to diet and water may influence performance, hatchability and intestinal bacterial load in Japanese quails with various feather colours. Objective: The aim of the study was to determine the effects of different doses of boric acid, supplemented in feed and water, on performance, hatchability and intestinal bacterial load in Japanese quails with different feather colours. Methods: A completely randomized 5 x 4 factorial design was implemented, consisting of five dietary treatments and four feather colour groups. The dietary treatments were control (basal diet without supplementation), F100 (100 mg/kg boric acid added to feed), F300 (300 mg/kg boric acid in feed), W100 (100 mg/L boric acid added to drinking water) and W300 (300 mg/L boric acid in water). A total of 300 Japanese quails (Coturnix coturnix japonica) with different feather colour genotypes-yellow (Y), white (W), grey (G) and black (B)-served as the experimental subjects. Each treatment group included 60 quails, with 15 individuals from each feather colour and experiment lasted for 90 days. Results: Supplementation of boric acid to feed and water did not affect egg production, feed consumption, feed conversion rate, viability or water consumption (p > 0.05). In the F300 group, hatchability from set eggs (p < 0.05) and from fertile eggs (p < 0.01) increased, whereas embryo mortality decreased significantly (p < 0.01). Compared to the control, total lactic acid bacteria count increased and coliform bacteria count decreased significantly in boric acid-supplemented groups (F300, W100 and W300) (p < 0.001). Egg production, feed conversion rate, viability, hatchability and intestinal bacterial load were similar among different feather colour varieties (p > 0.05). Feed consumption was highest in yellow and grey genotypes (p < 0.001). Conclusion: Boric acid can be used as a feed supplementation with positive effects on hatchability performance and intestinal health. Quail genotypes were generally similar in terms of the examined features.
Keywords: boric acid; gut health; hatchability; laying performance; quail; variety